2021
DOI: 10.1111/jocn.15842
|View full text |Cite
|
Sign up to set email alerts
|

What is and what ought to be: A meta‐synthesis of residential aged care staffs’ perspectives on quality care

Abstract: Background: As places of both residence and work, what constitutes "good quality care" in residential aged care requires consideration of staffs' perspectives.Objective: A meta-synthesis of the qualitative literature was conducted exploring residential aged care staff perspectives on "quality of care." Methods: Six electronic databases were searched for articles that met the screening inclusion criteria. This meta-synthesis was informed by the Preferred Reporting Items for Systematic reviews and Meta-Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
(260 reference statements)
0
5
0
Order By: Relevance
“…Consequently, we concluded that internal regulations can contribute to the provision of good quality of care and thus to the sustainable implementation of person-centred care. Other studies have discussed internal policies as instruments for facilitating or hindering person-centred care [ 39 ]. For internal policies to be significantly beneficial for staff, these regulations must find a balance according to which staff can comply with the policies while simultaneously providing dementia-specific person-centred care [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we concluded that internal regulations can contribute to the provision of good quality of care and thus to the sustainable implementation of person-centred care. Other studies have discussed internal policies as instruments for facilitating or hindering person-centred care [ 39 ]. For internal policies to be significantly beneficial for staff, these regulations must find a balance according to which staff can comply with the policies while simultaneously providing dementia-specific person-centred care [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Echoing the findings in this article, it can be epitomised by ‘being seen and respected as a person and … being informed and involved in one's own care and treatment’ (Nilsen et al, 2022, p. 573). Second, person‐centred care can be difficult to realise, largely due to limited resources, including time and competencies (Garratt et al, 2021; Watson & Hatcher, 2021). Extending previous research, this study demonstrates that despite the oft‐cited challenges that hinder quality aged care, brilliance happens.…”
Section: Discussionmentioning
confidence: 99%
“…Yet LTRC facilities remain highly structured work environments where the relational aspects of work that are key to person-centeredness can be perceived as not meeting the standard of "real work," which is bound up with instrumental values of linearity, abstraction, and rationality (Banerjee et al, 2021). The historically low station of LTRC in society has depended on the moral complexities and relational skills found beneath the surface and on the margins of "real work" failing to be accounted for (Garratt et al, 2021). Dissonance between tenets of person-centered philosophy and delivery of LTRC is reflected in the policy landscape which does not emphasize social care guidelines for building relationships (Hande, Keefe, & Taylor, 2021;Lowndes & Struthers, 2017).…”
Section: Centering Workers In Ltrc Reformmentioning
confidence: 99%
“…This finding is supported by work from Lightman (2021), who reported on interviews with immigrant women HCAs from Alberta and found that participants wished for their voices to be better understood and taken as integral to public conversations about reform and improvement of the LTRC sector. Similarly, Garratt et al's (2021) metasynthesis of LTRC staff perspectives on quality care found that staff positioned broader institutional and political contexts, government funding, regulation, and minimum staffing/training levels as occupying the space between "what is and what ought to be" in quality care (Garratt et al, 2021). Ideals of what workers know to be possible supply a promising source of engagement towards greater congruence between care realities, organizational cultures, and policy.…”
Section: Workers As Partners In Reformmentioning
confidence: 99%